Beyond Keywords: Automated Question Answering on the Web. - ROUSSINOV, DMITRI; WEIGUO FAN; ROBLES-FLORES, JOSÉ (Communications of the ACM, 2008)
The article discusses the Web search portal industry, examining the ability of computer programmers to develop completely automated open-domain question answering (QA) on the Web. The goal of QA, the authors indicate, is to take questions written by users in natural language and provide specific answers. Topics include questions on Google treated as 'bags,' or unordered sets of words, limited communication channels, and the high stock prices of search-portal companies. Also discussed are advances in open-domain (Web) QA.